Augmented Reality-Based Laptop Digital Catalog Application - Shiddqy Hidayat, Syahril; Taurusta, Cindy; Eviyanti, Ade; Senja Fitrani, Arif (International Journal on Human-Computing Studies, 2025)
Augmented Reality is a system that supports the real world with virtual (computer-generated) objects that appear together in the same space/place as the real world. One of the uses of Augmented Reality is as a promotional medium. The application of Augmented Reality (AR) in promotional media aims to increase the interest of consumers who are not satisfied with conventional promotional media. With conventional media, the attractiveness of an item is still not maximized. Based on the results of the research and the application made, it can be concluded that the "AR Laptop Catalog" application can help increase consumer interest by knowing the real form of the product and can help determine the desired laptop. The "AR Laptop Catalog" application was created with the aim of introducing Augmented Reality as a new promotional media, with the existence of AR-based promotional media it is hoped that it can be a reference for the development of further promotional media